Postharvest quality of Lepisanthes alata (Blume) Leenh. fruit harvested at three maturity stages - Anuar, M.; Lee, Yee Ling; Phebe, Ding (International Society for Horticultural Science, 2018)
Lepisanthes alata or locally known as ceri Terengganu is one of tropical exotic fruits and native to Malaysia. The discovery of this fruit is relatively new thus there is lack of reports available on the physicochemical characteristics of the fruit. A study was conducted to investigate fruit quality harvested at three maturity stages, i.e. green, half green-red and red. Changes in peel colour were observed where values of L* (lightness) and h° (hue) decreased significantly whereas C* (chroma) increased significantly as ripening progressed. Fruit firmness decreased significantly from 79.33 to 28.76 N as fruit ripened from green to red. Soluble solids concentration (SSC) of fruits increased from 11.28 to 13.61% while titratable acidity decreased as fruit matured and ripened. As the pH of ceri Terengganu fruit increased, the ascorbic acid content decreased significantly upon maturation and red stage contained the lowest ascorbic acid content at 5.36 mg 100 g-1. In conclusion, red stage ceri Terengganu fruit is palatable with soft texture and soluble solids concentration.